Estimation of evapotranspiration and single and dual crop coefficients of acai palm in the Eastern Amazon (Brazil) using the Bowen ratio system - Sousa, Denis de Pinho; Fernandes, Thiago Feliph Silva [UNESP]; Tavares, Lucas Belem; Farias, Vivian Dielly da Silva; Lima, Marcus Jose Alves de; Nunes, Hildo Giuseppe Garcia Caldas; Costa, Deborah Luciany Pires; Ortega-Farias, Samuel; Souza, Paulo Jorge de Oliveira Ponte (Springer, 2021)
The acai palm (Euterpe oleracea Mart.) is a fruit from the Amazon that is originally found in flooded areas. Over recent years, its marketability has gained significant interest in Brazil and abroad because of its agronomic, nutritional and economic potential. However, there is a lack of technical-scientific information about crop water requirements for irrigation management during the reproductive phase of acai palm. Therefore, the aim of this research was to estimate the water requirements (crop evapotranspiration (ETc), single (Kc) and dual (Kcb + Ke) crop coefficients) of acai palm in the Eastern Amazon (Brazil) using the Bowen ratio system. A micrometeorological tower was installed in the center of an experimental area to monitor ETc and meteorological variables. Phenological development was monitored during two growing seasons. Soil water evaporation was determined on a daily scale using weighing microlysimeters. Ke and Kcb values were calculated by the ratio of soil surface evaporation and transpiration to reference evapotranspiration (ETo), respectively. Total water requirements of the acai palms were 1165 mm, with a daily average of 3.49 mm day(-1) for the growing season. The average values of Kc, Ke and Kcb for the acai palm were 1.08; 0.21 and 0.84, respectively. The findings will assist the design of irrigation management protocols for acai trees that are better tailored to satisfy crop water requirements. This will allow improved water use efficiency, ensuring tree crop sustainability.